Characteristics of turbulence in the troposphere and lower stratosphere over the Indian Peninsula. (October 2015) - Sunilkumar, S.V.; Muhsin, M.; Parameswaran, K.; Venkat Ratnam, M.; Ramkumar, Geetha; Rajeev, K.; Krishna Murthy, B.V.; Sambhu Namboodiri, K.V.; Subrahmanyam, K.V.; Kishore Kumar, K.; Shankar Das, Siddarth
Abstract: Characteristics of turbulence in the troposphere and lower stratosphere at Trivandrum (8.5°N, 76.9°E) and Gadanki (13.5°N, 79.2°E), two tropical stations located in the Indian Peninsula, are studied using GPS-radiosonde observations during the period of December 2010 to March 2014 as part of the Tropical Tropopause Dynamics (TTD) Experiment under the CAWSES-India program. This study relies on the detection of turbulence applying Thorpe analysis to the temperature profile, taking into account the impact of atmospheric moisture and instrumental noise on static stability. In general, the tropospheric turbulence is largely intermittent in space and time. The altitude region very close to the convective tropopause (COT), 10–15 km, is relatively more turbulent than the lower troposphere from 3 to 8 km. Though the occurrence of turbulence decreases significantly above the COT, occasionally a rather thin layer of turbulence (thickness <1 km) is observed in the tropical tropopause layer (TTL) very close to the cold point tropopause (CPT). Even though broad turbulent layers, with thickness >2 km, are the persisting features that can be observed in the 5–15 km altitude region in multiple observations at both the sites at least during Asian Summer Monsoon (ASM) season, prominent multiple thin layers of stratified turbulence in the lower troposphere lasting for a day or less are observed only at Trivandrum in all seasons. In general, the turbulence strength in the 5–15 km altitude region at Gadanki is generally larger than that at Trivandrum. Below 15 km, while the turbulence is mainly governed by the convective instability at Gadanki, wind-shear driven (dynamic) instability also contributes considerably for the generation of turbulence at Trivandrum. While the generation of turbulence above 15 km is dominated by dynamic instability, in the lower stratosphere (LS) it is mainly due to strong wind shears. Highlights: Turbulence in the troposphere and LS were examined using radiosonde data over India. Altitude region 10-15 km is relatively more turbulent than in the 3 to 8 km. Occurrence of turbulence decreases significantly above convective tropopause. Turbulence in the 10-15 km region is mainly generated by convective instabilities. Turbulence in the TTL is generated by both dynamic and convective instabilities.